2004
DOI: 10.1097/01.ijg.0000137869.18156.81
|View full text |Cite
|
Sign up to set email alerts
|

Deep Sclerectomy Versus Punch Trabeculectomy with or without Phacoemulsification

Abstract: Both techniques, NPDS and PT, without enhancements (ie, implants or antimetabolites) control IOP efficaciously at our end point. Phacoemulsification combined with penetrating and non-penetrating procedures does not seem to interfere with final results. When a lower target IOP and probability of success over time are considered, PT, single or combined, exhibits a better trend. PT, therefore, could be more suitable for higher IOP levels or longer life expectancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
90
5
31

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(133 citation statements)
references
References 21 publications
7
90
5
31
Order By: Relevance
“…The low complication rate with low-dosage MMC in our sample is in agreement with our previous studies. 8,24,35,36 A recent pilot study 20 is not in agreement with our results, since it showed OLO to have a larger amount of complications than simple trabeculectomy. The conjunctival closure with two simple 10-0 nylon sutures at the flap extremities was probably responsible for a higher incidence of positive Seidel test with flat anterior chamber in the study group, and could have reduced the beneficial effect of the implant in bleb development.…”
Section: Discussioncontrasting
confidence: 54%
“…The low complication rate with low-dosage MMC in our sample is in agreement with our previous studies. 8,24,35,36 A recent pilot study 20 is not in agreement with our results, since it showed OLO to have a larger amount of complications than simple trabeculectomy. The conjunctival closure with two simple 10-0 nylon sutures at the flap extremities was probably responsible for a higher incidence of positive Seidel test with flat anterior chamber in the study group, and could have reduced the beneficial effect of the implant in bleb development.…”
Section: Discussioncontrasting
confidence: 54%
“…22 Several reports of NPGS describe combined cataract and glaucoma surgery with comparable or even better IOP-lowering outcomes. 14,17 To our knowledge, this case series represents the largest cohort with the longest follow-up of phaco-DS in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…16 Phacoemulsification combined with DS (phaco-DS) has been shown to be as effective as phacoemulsification with trabeculectomy (phaco-trab) in lowering IOP. 14,17 In this large case series, we seek to report the outcomes of phaco-DS from a single UK centre over a 10-year period. To our knowledge, this is the largest cohort to describe this procedure with such long-term follow-up results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pressure-reducing effect of penetrating surgery is probably still higher than that of non-penetrating strategies, particularly in the long run. [12][13][14] However, postoperative scarring is a major problem, compromising postoperative surgical success in both groups.…”
Section: Discussionmentioning
confidence: 99%